Protocolización, estandarización e interpretación de los valores y factores radiológicos de diagnóstico de rayos X digital CR en caninos atendidos en el Hospital Docente Veterinario César Augusto Guerrero de la Universidad Nacional de Loja - Peña Villalta, Fernando Paúl (2014)
This research work was carried out in the Veterinary Hospital Cesar Augusto Guerrero, in the radiology department; it had lasted four months, in this time was performed a radiographic file to 100 patients of different races and sizes that were assisted in the hospital. After the radiographic films were obtained, the interpretation of each one of these plates was done. For each radiographic the values of mAs and Kv were obtained, according to the system to develop the formula and to get the exposure time; with this information it is entered into the X-ray room to take the corresponding plate. Once the information on the X-ray plate has been interpreted, the diagnosis can be explained to the owner of the pet. The projections manual has a purpose that it is to know the different positions that can be adapted to take the radiological plates into the X-RAY room in the Veterinary Hospital. Also, to inform how the techniques should be performed to situated the patient in the projection table and obtained an X-ray plate understandable and diagnosable for professional and for the student. The safety and routines protocols, must be followed when entering in an X-ray room, so they will facilitate both, the handling and diagnosis of an X-ray plate